Evaluating the impact of seismic surveying on American plaice (Hippoglossoides platessoides) movement using acoustic telemetry in an offshore marine environment - Benjamin G.C. King; Khanh Q. Nguyen; Michael Piersiak; Pablo Borys; Coady Fitzpatrick; Jacqueline M. Hanlon; Dylan O'Neill; Corey J. Morris (Marine Pollution Bulletin, 2026)

Lung cancer risk in relation to indicative radon atlas metrics in Northern Ireland: a population-based case–control study using secondary data - Claire M. Delargy; Helen G. Coleman; Quentin G. Crowley; Damien Bennett; Javier Elio; Deirdre Fitzpatrick; Helen Mitchell; Sara M. Wallace; Rawan A. N. Alhattab; Angela Scott; Bernadette McGuinness; Ruth F. Hunter; et al. (Environmental Geochemistry and Health, 2026)
Radon is an established lung carcinogen, but more research is needed to inform whether area-based measures of radon exposure reflect underlying cancer risk. This study, the first of its kind in the UK, aimed to investigate the association between a nationwide indicative radon atlas and lung cancer risk in Northern Ireland, a region in which lung cancer screening programmes are under design. A population-based case–control study was conducted. Primary lung cancer cases ( n = 1,687) from the Northern Ireland Cancer Registry diagnosed in 2006 and 2014 were compared with 8,094 non-lung cancer controls from a large cohort. Radon exposure data were extracted from the Indicative Atlas of Radon, which categorises 1 km 2 areas by the percentage of households exceeding 200 Bq/m 3 . Exposure data were linked to participants by postcode. Logistic regression models adjusted for age, sex, smoking status, deprivation and PM 2.5 exposure were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for lung cancer. Individuals residing in high radon exposure areas (Atlas Class 6) had a greater than two-fold lung cancer risk (adjusted OR: 2.24, 95% CI: 1.25, 3.92) compared to residents in all other areas. This association was revealed after adjusting for PM 2.5 . This study supports the utility of an indicative radon atlas in reflecting underlying population lung cancer risk associated with radon, while highlighting constraints inherent to atlas-based exposure classification and secondary data.

Assessment of Fellowship Didactic Curricula in Hematology/Oncology: Cross-Sectional Findings From the PODCAST-HOF Trial - Ronak H. Mistry; Karine Tawagi; Daniel J. Hausrath; Samantha A. Armstrong; Inas A. Abuali; Ankoor N. Biswas; Srijan Valasapalli; Pranali S. Pachika; Moriah K. Forster; Ericson Stoen; Yurhee Lee; Giuliana G. Berardi; et al. (Journal of Cancer Education, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

High-altitude Martian plume is likely an ordinary twilight cloud - M.M.J. Crismani; M.S. Chaffin; K. Connour; N.M. Schneider; S. Curry; J. Deighan; R. Fitzpatrick; S. Jain; G. Liuzzi; M. Slipski; G.L. Villanueva (Icarus, 2026)

Mapping blue carbon ecosystems from Earth observations at a national scale for Papua New Guinea - Christopher J. Owers; Richard M. Lucas; Carole Planque; Daniel Clewley; Matt Paget; Chloe Fitzpatrick; Annette Burke; Freddie Alei; Mitchell B. Lyons; Andrew D. L. Steven (Frontiers in Marine Science, 2025)
National maps are essential to support the conservation, restoration, and sustainable management of blue carbon ecosystems (BCE). This is particularly important for nations in the Indo-Pacific region, including Papua New Guinea (PNG), that aspire to integrate these ecosystems into their nationally determined contributions (NDCs) for ecosystem accounting. This study focussed on mapping the extent of BCEs in PNG using Earth observation data for the year 2020 and reporting on biomass and carbon storage services. Land cover categories were generated using the Living Earth framework for the 15 coastal provinces of PNG. The total BCE area in PNG (14,353 km²) comprised 30% mangrove, 65% lowland peat swamp forest, 3% saltmarsh, and 2% seagrass. Lowland peat swamp forests contribute the greatest biomass (137.94 ± 67.10 Tg) followed by mangroves (71.79 ± 27.16 Tg), with a total biomass of 212.99 ± 95.89 Tg. Across PNG, a total of 710.46 ± 362.75 Tg C were estimated for belowground carbon of BCEs (reporting to 1 m depth), almost seven times more than that of aboveground carbon (102.14 ± 45.97 Tg C). This study highlights the need for a consistent and standardised framework for mapping BCEs, which can support coordinated management of coastal landscapes across provinces that contribute to national policies and NDC reporting. This case study can be used as a demonstration for other nations where similar opportunities and challenges may exist for mapping BCE using Earth observations, with a framework that can be compared and adapted to user requirements.

Evaluating uncertainties with sample-collection method and source selection in sediment fingerprinting: an example from a Great Lakes tributary - Tanja N. Williamson; James D. Blount; Heidi M. Broerman; Faith A. Fitzpatrick; Isaac J. Mevis; Dayle J. Hoefling; Shannon M. Pace; Matthew J. Komiskey; Rebecca M. Kreiling (Journal of Soils and Sediments, 2025)
Purpose Identifying suspended-sediment (SS) sources, seasonal variability, and phosphorus (P) transported with SS is critical information for basin managers, although there may be concerns about comparability between flow-integrated SS samples used for sediment fingerprinting and discrete samples used for concentrations and loads in basins where SS is mostly silt + clay and(or) one land-use predominates. Objectives were to determine if (1) sample-collection method and (2) source consideration influenced apportionment of the largest SS source. Methods Concurrent-replicate, SS samples were collected during 2022 from the East River, Wisconsin using an automated sampler, commonly used for water-quality sampling, and passive samplers, frequently used for SS fingerprinting. Samples were evaluated for differences in physical and chemical characteristics that may affect source apportionment. Considered sources included three upland land-use (cropland, forest, and roads), two in-channel (streambank and streambed sediment), and one that connects uplands to the stream channel (gullies). Source apportionment used established methods in the SedSAT tool. Source scenarios included land-use + streambank (4src), 4src + gully, 4src + streambed, and 4src + gully + streambed (6src). Results There were no statistically significant differences in median grain size, organic carbon, or sediment-bound P as a function of collection method. In-channel sources were the largest proportional SS source, regardless of season, hydrologic condition, collection method, or source scenario. Source verification highlighted which source fingerprints were most accurately defined and implications for SS target apportionment. Conclusion Varying the source scenarios for sediment fingerprinting indicated that improved management of hydrologic connectivity between upland land use and the stream channel has the potential to mitigate SS loads.

Community engagement in the context of cancer: scoping review of definitions and measures to inform program-level analysis - Heidi J. Keeler; Regina Idoate; Brooke J. Fitzpatrick; Emma Hymel; Josiane Kabayundo; Krishtee Napit; Cynthia M. Schmidt; Shinobu Watanabe-Galloway (Cancer Causes & Control, 2025)

Pyrethroid insecticide pollution of wetlands reduces amphipod density - Breanna R. Keith; Danelle M. Larson; Carl W. Isaacson; Michael J. Anteau; Megan J. Fitzpatrick; Jake D. Carleen (Ecotoxicology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Rationale and design of the Dog Aging Project precision cohort: a multi-omic resource for longitudinal research in geroscience - Jena Prescott; Amber J. Keyser; Paul Litwin; Matthew D. Dunbar; Robyn McClelland; Audrey Ruple; Holley Ernst; Brianna L. Butler; Mandy Kauffman; Anne Avery; Benjamin R. Harrison; Maria Partida-Aguilar; et al. (GeroScience, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Species identification of modern and archaeological shark and ray skeletal tissues using collagen peptide mass fingerprinting - Michael Buckley; Ellie-May Oldfield; Cristina Oliveira; Clara Boulanger; Andrew C. Kitchener; Nicole R. Fuller; Traci Ardren; Victor D. Thompson; Scott M. Fitzpatrick; Michelle J. LeFebvre (Frontiers in Marine Science, 2024)
Introduction Elasmobranchs, such as sharks and rays, are among the world’s most endangered vertebrates, with over 70% loss in abundance over the past 50 years due to human impacts. Zooarchaeological baselines of elasmobranch diversity, distribution, and exploitation hold great promise for contributing essential historical contexts in the assessment of contemporary patterns in their taxonomic diversity and vulnerability to human-caused extinction. Yet, the historical ecology of elasmobranchs receives relatively less archaeological attention compared to that of ray-finned fishes or marine mammals, largely due to issues of taxonomic resolution across zooarchaeological identifications. Methods We explore the use of Zooarchaeology by Mass Spectrometry (ZooMS) for species identification in this unstudied group, using an archaeological case study from the marine environments of the Florida Keys, a marine biodiversity hotspot that is home to an array of elasmobranch species and conservation efforts. By comparison with 39 modern reference species, we could distinguish 12 taxa within the zooarchaeological assemblage from the Clupper archaeological site (Upper Matecumbe Key) that included nine sharks, two rays and a sawfish. Results and discussion The results indicate that, through additional complexity of the collagen peptide mass fingerprint, obtained due to the presence of the cartilaginous type II collagen, ZooMS collagen peptide mass fingerprinting provides exceptionally high taxonomic resolution in this group, yielding species-level identifications in all cases where sufficient reference material was used. This case study also highlights the added value of ZooMS for taxa that are more difficult to distinguish in zooarchaeological analyses, such as vertebrae of the Atlantic sharpnose shark ( Rhizoprionodon terraenovae ) and the hammerhead sharks ( Sphyrna spp.) in the Florida Keys. Therefore, the application of collagen peptide mass fingerprinting to elasmobranchs offers great potential to improve our understanding of their archaeological past and historical ecology.

Cheddar cheese production, structure and in-vitro semi-dynamic gastric digestion: The role of β-casein phenotype - Davor Daniloski; Richard M. Page; Prabin Lamichhane; Conor J. Fitzpatrick; Todor Vasiljevic; André Brodkorb; Mark Timlin; John Paul Murphy; Tom F. O'Callaghan; Noel A. McCarthy (Food Research International, 2024)

A novel in vitro high-content imaging assay for the prediction of drug-induced lung toxicity - Paul A. Fitzpatrick; Julia Johansson; Gareth Maglennon; Ian Wallace; Ramon Hendrickx; Marianna Stamou; Kinga Balogh Sivars; Susann Busch; Linnea Johansson; Natalie Van Zuydam; Kelley Patten; Per M. Åberg; et al. (Archives of Toxicology, 2024)
The development of inhaled drugs for respiratory diseases is frequently impacted by lung pathology in non-clinical safety studies. To enable design of novel candidate drugs with the right safety profile, predictive in vitro lung toxicity assays are required that can be applied during drug discovery for early hazard identification and mitigation. Here, we describe a novel high-content imaging-based screening assay that allows for quantification of the tight junction protein occludin in A549 cells, as a model for lung epithelial barrier integrity. We assessed a set of compounds with a known lung safety profile, defined by clinical safety or non-clinical in vivo toxicology data, and were able to correctly identify 9 of 10 compounds with a respiratory safety risk and 9 of 9 compounds without a respiratory safety risk (90% sensitivity, 100% specificity). The assay was sensitive at relevant compound concentrations to influence medicinal chemistry optimization programs and, with an accessible cell model in a 96-well plate format, short protocol and application of automated imaging analysis algorithms, this assay can be readily integrated in routine discovery safety screening to identify and mitigate respiratory toxicity early during drug discovery. Interestingly, when we applied physiologically-based pharmacokinetic (PBPK) modelling to predict epithelial lining fluid exposures of the respiratory tract after inhalation, we found a robust correlation between in vitro occludin assay data and lung pathology in vivo, suggesting the assay can inform translational risk assessment for inhaled small molecules.

Fish Invasion of Prairie Pothole Wetlands Reduces Amphipod Abundance, A Key Vertebrate Forage - Jake D. Carleen; Danelle M. Larson; Michael J. Anteau; Megan J. Fitzpatrick; Andrew W. Hafs; Carl W. Isaacson; Breanna R. Keith (Wetlands, 2024)

Genetic structure of restored Brook Trout populations in the Southern Appalachian Mountains indicates successful reintroductions - Rebecca J. Smith; David C. Kazyak; Matt A. Kulp; Barbara A. Lubinski; Benjamin M. Fitzpatrick (Conservation Genetics, 2024)

Mechanistic safety assessment via multi-omic characterisation of systemic pathway perturbations following in vivo MAT2A inhibition - Valentina Fogal; Filippos Michopoulos; Andrew F. Jarnuczak; Ghaith M. Hamza; Stephanie Harlfinger; Paul Davey; Heather Hulme; Stephen J. Atkinson; Piotr Gabrowski; Tony Cheung; Michael Grondine; Clare Hoover; et al. (Archives of Toxicology, 2024)
The tumour suppressor p16/CDKN2A and the metabolic gene, methyl-thio-adenosine phosphorylase (MTAP), are frequently co-deleted in some of the most aggressive and currently untreatable cancers. Cells with MTAP deletion are vulnerable to inhibition of the metabolic enzyme, methionine-adenosyl transferase 2A (MAT2A), and the protein arginine methyl transferase (PRMT5). This synthetic lethality has paved the way for the rapid development of drugs targeting the MAT2A/PRMT5 axis. MAT2A and its liver- and pancreas-specific isoform, MAT1A, generate the universal methyl donor S-adenosylmethionine (SAM) from ATP and methionine. Given the pleiotropic role SAM plays in methylation of diverse substrates, characterising the extent of SAM depletion and downstream perturbations following MAT2A/MAT1A inhibition (MATi) is critical for safety assessment. We have assessed in vivo target engagement and the resultant systemic phenotype using multi-omic tools to characterise response to a MAT2A inhibitor (AZ’9567). We observed significant SAM depletion and extensive methionine accumulation in the plasma, liver, brain and heart of treated rats, providing the first assessment of both global SAM depletion and evidence of hepatic MAT1A target engagement. An integrative analysis of multi-omic data from liver tissue identified broad perturbations in pathways covering one-carbon metabolism, trans-sulfuration and lipid metabolism. We infer that these pathway-wide perturbations represent adaptive responses to SAM depletion and confer a risk of oxidative stress, hepatic steatosis and an associated disturbance in plasma and cellular lipid homeostasis. The alterations also explain the dramatic increase in plasma and tissue methionine, which could be used as a safety and PD biomarker going forward to the clinic.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Equivalent roles of marine subsidies and island characteristics in shaping island bird communities - Debora S. Obrist; Patrick J. Hanly; Jeremiah C. Kennedy; Owen T. Fitzpatrick; Sara B. Wickham; Wiebe Nijland; Luba Y. Reshitnyk; Chris T. Darimont; Brian M. Starzomski; John D. Reynolds (Journal of Biogeography, 2024)
Aim Species distributions across islands are shaped by dispersal limitations, environmental filters and biotic interactions but the relative influence of each of these processes has rarely been assessed. Here, we examine the relative contributions of island characteristics, marine subsidies, species traits, and species interactions on avian community composition. Location Central Coast region of British Columbia, Canada. Taxon Terrestrial breeding birds. Methods We observed 3610 individuals of 32 bird species on 89 islands that spanned multiple orders of magnitude in area (0.0002–3 km 2 ). We fit a spatially explicit joint species distribution model to estimate the relative contributions of island physical characteristics, island‐specific inputs of marine subsidies, species' traits, and biotic interactions on species distributions. Biogeographic characteristics included island area, isolation, and habitat heterogeneity, while marine influence was represented by forest‐edge soil δ 15 N, wrack biomass, shoreline substrate, and distance to shore. This approach also allowed us to estimate how much variation in distributions resulted from species' biological traits (i.e. body mass, feeding guild, feeding height, and nesting height). Results Bird species distributions were determined almost equivalently by island biogeographic characteristics (23.5% of variation explained) and marine influence (24.8%). We detected variation in species‐specific responses to both island biogeographic characteristics and marine influence, but no significant effect of any biological trait examined. Additionally, we found evidence that habitat preferences were a more important driver than competitive interactions. Main Conclusions Although most island biogeographic studies focus only on islands' physical characteristics, we found evidence for an equivalent role of marine subsidy in structuring island bird communities. Our study suggests that for small islands, disentangling the effects of island biogeographic characteristics, marine inputs, and biotic interactions is a useful next step in understanding species distributions.

Terrestrial carbon isotope stratigraphy of the Eocene–Oligocene transition, Petrockstowe and Bovey basins, Devon, UK - Mohammed S. Chaanda; Stephen T. Grimes; Rhodri M. Jerrett; Mark Anderson; Melanie J. Leng; Meriel E. Fitzpatrick; Gregory D. Price (Proceedings of the Geologists' Association, 2023)

Parallel evaluation of alternative skin barrier models and excised human skin for dermal absorption studies in vitro - Alec T. Salminen; Kelly J. Davis; Robert P. Felton; Nathania Nischal; Linda S. VonTungeln; Frederick A. Beland; Kristy Derr; Paul C. Brown; Marc Ferrer; Linda M. Katz; Nicole C. Kleinstreuer; Jonathan Leshin; et al. (Toxicology in Vitro, 2023)

Mapping soil corrosivity in an Australian arid environment and comparing corrosion rates of exclusion fence netting with different zinc coatings - Andrea D. Stiglingh; Luke M. Mosley; Ronald J. Smernik; Robert W. Fitzpatrick (Geoderma Regional, 2023)

Evaluation of a Prefabricated Fish Passage Design for Great Plains Fishes - Ryan M. Fitzpatrick; David W. Longrie; Ryan J. Friebertshauser; H. Paul Foutz (Fishes, 2023)
Connectivity is critical for stream fish persistence, and fish passage structures are a useful conservation tool to reconnect fragmented systems. The design of fish passage structures is a tradeoff between the area available for construction, slope, and costs associated with the structure. The Longrie–Fecteau fish passage structure was designed to be modular, adjustable to barrier-specific needs, and to have a low slope (2%) to pass small-bodied fishes. We evaluated fish passage through this structure in Fountain Creek, Colorado, USA, via a PIT tag mark–recapture study. We documented four native Great Plains fish species successfully ascending the passage structure, with most passage occurring at night. We estimated a 3% probability of a released fish entering the structure, then 89% and 99% passage to the midpoint and exit of the 123 m structure, respectively. Low entrance efficiency was due to low recapture probability of small-bodied study organisms in a relatively large system, and the low percentage of space of the entryway on this barrier (

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Size-Dependent Effective Diffusivity in Healthy Human and Porcine Joint Synovium - Young Guang; Alexandra L. Davis; Thomas M. McGrath; Christine T. N. Pham; James A. J. Fitzpatrick; Lori A. Setton (Annals of Biomedical Engineering, 2022)

High abundance of a single taxon (amphipods) predicts aquatic macrophyte biodiversity in prairie wetlands - Danelle M. Larson; Demey DeJong; Michael J. Anteau; Megan J. Fitzpatrick; Breanna Keith; Emily G. Schilling; Barry Thoele (Biodiversity and Conservation, 2022)
Conservation programs often aim to protect the abundance of individual species and biodiversity simultaneously. We quantified relations between amphipod densities and aquatic macrophyte (large plants and algae) diversity to test a hypothesis that biodiversity can support high abundance of a single taxonomic group. Amphipods ( Gammarus lacustris and Hyalella azteca ) are key forage for waterfowl and are declining in the Prairie Pothole Region of North America. We sampled a large gradient of amphipod densities (0–7050 amphipods/m 3 ) in 49 semi-permanent wetlands, and 50% of the study wetlands had high amphipod densities (> 500 amphipods/m 3 ). Generalized linear models revealed G. lacustris and H. azteca densities increased exponentially with macrophyte diversity indices. Further, H. azteca densities were greatest at moderate levels of submersed vegetation biomass. Community analyses showed both amphipod species were positively associated with diverse macrophyte assemblages and negatively associated with high coverage of cattails ( Typha spp.), a taxon that creates monotypic stands, as well as bladderwort ( Utricularia spp.), a carnivorous plant. Our results indicate that amphipods could be used as an umbrella species for protecting diverse macrophyte communities in semi-permanent and permanent wetlands of North America’s Prairie Pothole Region.

Advancing Social Equity in and Through Marine Conservation - Nathan J. Bennett; Laure Katz; Whitney Yadao-Evans; Gabby N. Ahmadia; Scott Atkinson; Natalie C. Ban; Neil M. Dawson; Asha de Vos; Juno Fitzpatrick; David Gill; Mael Imirizaldu; Naia Lewis; et al. (Frontiers in Marine Science, 2021)
Substantial efforts and investments are being made to increase the scale and improve the effectiveness of marine conservation globally. Though it is mandated by international law and central to conservation policy, less attention has been given to how to operationalize social equity in and through the pursuit of marine conservation. In this article, we aim to bring greater attention to this topic through reviewing how social equity can be better integrated in marine conservation policy and practice. Advancing social equity in marine conservation requires directing attention to: recognition through acknowledgment and respect for diverse peoples and perspectives; fair distribution of impacts through maximizing benefits and minimizing burdens; procedures through fostering participation in decision-making and good governance; management through championing and supporting local involvement and leadership; the environment through ensuring the efficacy of conservation actions and adequacy of management to ensure benefits to nature and people; and the structural barriers to and institutional roots of inequity in conservation. We then discuss the role of various conservation organizations in advancing social equity in marine conservation and identify the capacities these organizations need to build. We urge the marine conservation community, including governments, non-governmental organizations and donors, to commit to the pursuit of socially equitable conservation.

Do skeletal muscle motor units and microvascular units align to help match blood flow to metabolic demand? - Coral L. Murrant; Nicole M. Fletcher; Eamon J. H. Fitzpatrick; Kinley S. Gee (European Journal of Applied Physiology, 2021)

Size-Dependent Effective Diffusivity in Healthy Human and Porcine Joint Synovium - Young Guang; Alexandra L. Davis; Thomas M. McGrath; Christine T. N. Pham; James A. J. Fitzpatrick; Lori A. Setton (Annals of Biomedical Engineering, 2021)

Can indicator species guide conservation investments to restore connectivity in Great Lakes tributaries? - Kimberly B. Fitzpatrick; Allison T. Moody; Austin Milt; Matthew E. Herbert; Mary Khoury; Eugene Yacobson; Jared A. Ross; Patrick J. Doran; Michael C. Ferris; Peter B. McIntyre; Thomas M. Neeson (Biodiversity and Conservation, 2021)

Snowpack, Tree Size, and Ecological Legacies Promote Seedling Establishment in Tree Islands at the Treeline - O. T. Fitzpatrick; M. Blade; L. A. Fishback; G. P. Kershaw; J. Muffly; S. D. Mamet (Ecosystems, 2020)

Effects of the cannabinoid receptor agonist CP-55,940 on incentive salience attribution - Ali Gheidi; Lora M. Cope; Christopher J. Fitzpatrick; Benjamin N. Froehlich; Rachel Atkinson; Coltrane K. Groves; Clair N. Barcelo; Jonathan D. Morrow (Psychopharmacology, 2020)

Delineation of phenotypes and genotypes related to cohesin structural protein RAD21 - Lianne C. Krab; Iñigo Marcos-Alcalde; Melissa Assaf; Meena Balasubramanian; Janne Bayer Andersen; Anne-Marie Bisgaard; David R. Fitzpatrick; Sanna Gudmundsson; Sylvia A. Huisman; Tugba Kalayci; Saskia M. Maas; Francisco Martinez; et al. (Human Genetics, 2020)
RAD21 encodes a key component of the cohesin complex, and variants in RAD21 have been associated with Cornelia de Lange Syndrome (CdLS). Limited information on phenotypes attributable to RAD21 variants and genotype–phenotype relationships is currently published. We gathered a series of 49 individuals from 33 families with RAD21 alterations [24 different intragenic sequence variants (2 recurrent), 7 unique microdeletions], including 24 hitherto unpublished cases. We evaluated consequences of 12 intragenic variants by protein modelling and molecular dynamic studies. Full clinical information was available for 29 individuals. Their phenotype is an attenuated CdLS phenotype compared to that caused by variants in NIPBL or SMC1A for facial morphology, limb anomalies, and especially for cognition and behavior. In the 20 individuals with limited clinical information, additional phenotypes include Mungan syndrome (in patients with biallelic variants) and holoprosencephaly, with or without CdLS characteristics. We describe several additional cases with phenotypes including sclerocornea, in which involvement of the RAD21 variant is uncertain. Variants were frequently familial, and genotype–phenotype analyses demonstrated striking interfamilial and intrafamilial variability. Careful phenotyping is essential in interpreting consequences of RAD21 variants, and protein modeling and dynamics can be helpful in determining pathogenicity. The current study should be helpful when counseling families with a RAD21 variation.

Translational studies of intravenous and intracerebroventricular routes of administration for CNS cellular biodistribution for BMN 250, an enzyme replacement therapy for the treatment of Sanfilippo type B - Anita Grover; Danielle Crippen-Harmon; Lacey Nave; Jon Vincelette; Jill C. M. Wait; Andrew C. Melton; Roger Lawrence; Jillian R. Brown; Katherine A. Webster; Bryan K. Yip; Brian Baridon; Catherine Vitelli; et al. (Drug Delivery and Translational Research, 2020)
BMN 250 is being developed as enzyme replacement therapy for Sanfilippo type B, a primarily neurological rare disease, in which patients have deficient lysosomal alpha- N -acetylglucosaminidase (NAGLU) enzyme activity. BMN 250 is taken up in target cells by the cation-independent mannose 6-phosphate receptor (CI-MPR, insulin-like growth factor 2 receptor), which then facilitates transit to the lysosome. BMN 250 is dosed directly into the central nervous system via the intracerebroventricular (ICV) route, and the objective of this work was to compare systemic intravenous (IV) and ICV delivery of BMN 250 to confirm the value of ICV dosing. We first assess the ability of enzyme to cross a potentially compromised blood–brain barrier in the Naglu −/− mouse model and then assess the potential for CI-MPR to be employed for receptor-mediated transport across the blood–brain barrier. In wild-type and Naglu −/− mice, CI-MPR expression in brain vasculature is high during the neonatal period but virtually absent by adolescence. In contrast, CI-MPR remains expressed through adolescence in non-affected non-human primate and human brain vasculature. Combined results from IV administration of BMN 250 in Naglu −/− mice and IV and ICV administration in healthy juvenile non-human primates suggest a limitation to therapeutic benefit from IV administration because enzyme distribution is restricted to brain vascular endothelial cells: enzyme does not reach target neuronal cells following IV administration, and pharmacological response following IV administration is likely restricted to clearance of substrate in endothelial cells. In contrast, ICV administration enables central nervous system enzyme replacement with biodistribution to target cells.

Temperature and telomeres: thermal treatment influences telomere dynamics through a complex interplay of cellular processes in a cold-climate skink - L. J. Fitzpatrick; M. Olsson; L. M. Parsley; A. Pauliny; T. L. Pinfold; T. Pirtle; G. M. While; E. Wapstra (Oecologia, 2019)

Dominance–diversity relationships in ant communities differ with invasion - Xavier Arnan; Alan N. Andersen; Heloise Gibb; Catherine L. Parr; Nathan J. Sanders; Robert R. Dunn; Elena Angulo; Fabricio B. Baccaro; Tom R. Bishop; Raphaël Boulay; Cristina Castracani; Xim Cerdá; et al. (Global Change Biology, 2018)
The relationship between levels of dominance and species richness is highly contentious, especially in ant communities. The dominance‐impoverishment rule states that high levels of dominance only occur in species‐poor communities, but there appear to be many cases of high levels of dominance in highly diverse communities. The extent to which dominant species limit local richness through competitive exclusion remains unclear, but such exclusion appears more apparent for non‐native rather than native dominant species. Here we perform the first global analysis of the relationship between behavioral dominance and species richness. We used data from 1,293 local assemblages of ground‐dwelling ants distributed across five continents to document the generality of the dominance‐impoverishment rule, and to identify the biotic and abiotic conditions under which it does and does not apply. We found that the behavioral dominance–diversity relationship varies greatly, and depends on whether dominant species are native or non‐native, whether dominance is considered as occurrence or relative abundance, and on variation in mean annual temperature. There were declines in diversity with increasing dominance in invaded communities, but diversity increased with increasing dominance in native communities. These patterns occur along the global temperature gradient. However, positive and negative relationships are strongest in the hottest sites. We also found that climate regulates the degree of behavioral dominance, but differently from how it shapes species richness. Our findings imply that, despite strong competitive interactions among ants, competitive exclusion is not a major driver of local richness in native ant communities. Although the dominance‐impoverishment rule applies to invaded communities, we propose an alternative dominance‐diversification rule for native communities.

Conserving rare species can have high opportunity costs for common species - Thomas M. Neeson; Patrick J. Doran; Michael C. Ferris; Kimberly B. Fitzpatrick; Matthew Herbert; Mary Khoury; Allison T. Moody; Jared Ross; Eugene Yacobson; Peter B. McIntyre (Global Change Biology, 2018)
Conservation practitioners face difficult choices in apportioning limited resources between rare species (to ensure their existence) and common species (to ensure their abundance and ecosystem contributions). We quantified the opportunity costs of conserving rare species of migratory fishes in the context of removing dams and retrofitting road culverts across 1,883 tributaries of the North American Great Lakes. Our optimization models show that maximizing total habitat gains across species can be very efficient in terms of benefits achieved per dollar spent, but disproportionately benefits common species. Conservation approaches that target rare species, or that ensure some benefits for every species (i.e., complementarity) enable strategic allocation of resources among species but reduce aggregate habitat gains. Thus, small habitat gains for the rarest species necessarily come at the expense of more than 20 times as much habitat for common ones. These opportunity costs are likely to occur in many ecosystems because range limits and conservation costs often vary widely among species. Given that common species worldwide are declining more rapidly than rare ones within major taxa, our findings provide incentive for triage among multiple worthy conservation targets.

Golden Eagle fatalities and the continental‐scale consequences of local wind‐energy generation - Todd E. Katzner; David M. Nelson; Melissa A. Braham; Jacqueline M. Doyle; Nadia B. Fernandez; Adam E. Duerr; Peter H. Bloom; Matthew C. Fitzpatrick; Tricia A. Miller; Renee C. E. Culver; Loan Braswell; J. Andrew DeWoody (Conservation Biology, 2017)
Renewable energy production is expanding rapidly despite mostly unknown environmental effects on wildlife and habitats. We used genetic and stable isotope data collected from Golden Eagles (Aquila chrysaetos) killed at the Altamont Pass Wind Resource Area (APWRA) in California in demographic models to test hypotheses about the geographic extent and demographic consequences of fatalities caused by renewable energy facilities. Geospatial analyses of δ 2 H values obtained from feathers showed that ≥25% of these APWRA‐killed eagles were recent immigrants to the population, most from long distances away (>100 km). Data from nuclear genes indicated this subset of immigrant eagles was genetically similar to birds identified as locals from the δ 2 H data. Demographic models implied that in the face of this mortality, the apparent stability of the local Golden Eagle population was maintained by continental‐scale immigration. These analyses demonstrate that ecosystem management decisions concerning the effects of local‐scale renewable energy can have continental‐scale consequences.

Theory of Visual Attention (TVA) applied to mice in the 5-choice serial reaction time task - C. M. Fitzpatrick; M. Caballero-Puntiverio; U. Gether; T. Habekost; C. Bundesen; S. Vangkilde; D. P. D. Woldbye; J. T. Andreasen; A. Petersen (Psychopharmacology, 2017)

A global database of ant species abundances - Heloise Gibb; Rob R. Dunn; Nathan J. Sanders; Blair F. Grossman; Manoli Photakis; Silvia Abril; Donat Agosti; Alan N. Andersen; Elena Angulo; Inge Armbrecht; Xavier Arnan; Fabricio B. Baccaro; et al. (Ecology, 2017)
What forces structure ecological assemblages? A key limitation to general insights about assemblage structure is the availability of data that are collected at a small spatial grain (local assemblages) and a large spatial extent (global coverage). Here, we present published and unpublished data from 51 ,388 ant abundance and occurrence records of more than 2,693 species and 7,953 morphospecies from local assemblages collected at 4,212 locations around the world. Ants were selected because they are diverse and abundant globally, comprise a large fraction of animal biomass in most terrestrial communities, and are key contributors to a range of ecosystem functions. Data were collected between 1949 and 2014, and include, for each geo‐referenced sampling site, both the identity of the ants collected and details of sampling design, habitat type, and degree of disturbance. The aim of compiling this data set was to provide comprehensive species abundance data in order to test relationships between assemblage structure and environmental and biogeographic factors. Data were collected using a variety of standardized methods, such as pitfall and Winkler traps, and will be valuable for studies investigating large‐scale forces structuring local assemblages. Understanding such relationships is particularly critical under current rates of global change. We encourage authors holding additional data on systematically collected ant assemblages, especially those in dry and cold, and remote areas, to contact us and contribute their data to this growing data set.

A longitudinal study of patients with cirrhosis treated with L-ornithine L-aspartate, examined with magnetization transfer, diffusion-weighted imaging and magnetic resonance spectroscopy - Vijay P. B. Grover; Mark J. W. McPhail; Marzena Wylezinska-Arridge; Mary M. E. Crossey; Julie A. Fitzpatrick; Louise Southern; Brian K. Saxby; Nicola A. Cook; I. Jane Cox; Adam D. Waldman; Novraj S. Dhanjal; Aluel Bak-Bol; et al. (Metabolic Brain Disease, 2017)

An experimental test of relatedness-based mate discrimination in a social lizard - Genevieve Bordogna; George Cunningham; Luisa J. Fitzpatrick; Ben Halliwell; Hannah E. A. MacGregor; Kirke L. Munch; Erik Wapstra; Geoffrey M. While (Behavioral Ecology and Sociobiology, 2016)

A comparative review of fisheries management experiences in the E uropean U nion and in other countries worldwide: I celand, A ustralia, and N ew Z ealand - Paul Marchal; Jesper Levring Andersen; Martin Aranda; Mike Fitzpatrick; Leyre Goti; Olivier Guyader; Gunnar Haraldsson; Aaron Hatcher; Troels Jacob Hegland; Pascal Le Floc'h; Claire Macher; Loretta Malvarosa; et al. (Fish and Fisheries, 2016)
This study compares the details and performance of fisheries management between the EU and a selection of other countries worldwide: Iceland, New Zealand, and Australia, which are considered in many respects to be among the most advanced in the world in fisheries management. Fisheries management in the EU , Iceland, Australia, and New Zealand has developed following different paths, despite being based on similar instruments and principles. Iceland, Australia, and New Zealand have been at the forefront of developing management practices such as stakeholder involvement, legally binding management targets (Australia, New Zealand), individual transferable quotas, and discard bans (Iceland, New Zealand). The EU has since the beginning of the 21st century taken significant steps to better involve stakeholders and establish quantitative targets through management plans, and a landing obligation is gradually being implemented from 2015 onward. The management of domestic fisheries resources in Australia, New Zealand, and Iceland has, overall, performed better than in the EU , in terms of conservation and economic efficiency. It should, however, be stressed that, compared to Australia, New Zealand, and Iceland, (i) initial over‐capacity was more of an issue in the EU when management measures became legally binding and also that (ii) EU has been progressive in developing common enforcement standards, on stocks shared by sovereign nations. The situation of EU fisheries has substantially improved over the period 2004–2013 in the northeast Atlantic, with fishery status getting close to that in the other jurisdictions, but the lack of recovery for Mediterranean fish stocks remains a concern.

Exercise training comprising of single 20-s cycle sprints does not provide a sufficient stimulus for improving maximal aerobic capacity in sedentary individuals - P. Songsorn; A. Lambeth-Mansell; J. L. Mair; M. Haggett; B. L. Fitzpatrick; J. Ruffino; A. Holliday; R. S. Metcalfe; N. B. J. Vollaard (European Journal of Applied Physiology, 2016)

Initial evaluations of a Gulf of Mexico/Caribbean ocean forecast system in the context of the Deepwater Horizon disaster - Edward D. Zaron; Patrick J. Fitzpatrick; Scott L. Cross; John M. Harding; Frank L. Bub; Jerry D. Wiggert; Dong S. Ko; Yee Lau; Katharine Woodard; Christopher N. K. Mooers (Frontiers of Earth Science, 2015)

Locally adapted traits maintained in the face of high gene flow - S. W. Fitzpatrick; J. C. Gerberich; J. A. Kronenberger; L. M. Angeloni; W. C. Funk (Ecology Letters, 2015)
Gene flow between phenotypically divergent populations can disrupt local adaptation or, alternatively, may stimulate adaptive evolution by increasing genetic variation. We capitalised on historical Trinidadian guppy transplant experiments to test the phenotypic effects of increased gene flow caused by replicated introductions of adaptively divergent guppies, which were translocated from high‐ to low‐predation environments. We sampled two native populations prior to the onset of gene flow, six historic introduction sites, introduction sources and multiple downstream points in each basin. Extensive gene flow from introductions occurred in all streams, yet adaptive phenotypic divergence across a gradient in predation level was maintained. Descendants of guppies from a high‐predation source site showed high phenotypic similarity with native low‐predation guppies in as few as ~12 generations after gene flow, likely through a combination of adaptive evolution and phenotypic plasticity. Our results demonstrate that locally adapted phenotypes can be maintained despite extensive gene flow from divergent populations.

Aspirated bile: a major host trigger modulating respiratory pathogen colonisation in cystic fibrosis patients - F. J. Reen; D. F. Woods; M. J. Mooij; M. N. Chróinín; D. Mullane; L. Zhou; J. Quille; D. Fitzpatrick; J. D. Glennon; G. P. McGlacken; C. Adams; F. O’Gara (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Adult vascular smooth muscle cells in culture express neural stem cell markers typical of resident multipotent vascular stem cells - Eimear Kennedy; Ciaran J. Mooney; Roya Hakimjavadi; Emma Fitzpatrick; Shaunta Guha; Laura E. Collins; Christine E. Loscher; David Morrow; Eileen M. Redmond; Paul A. Cahill (Cell and Tissue Research, 2014)

Coping with aquatic hypoxia: how the plainfin midshipman (Porichthys notatus) tolerates the intertidal zone - Paul M. Craig; John L. Fitzpatrick; Patrick J. Walsh; Chris M. Wood; Grant B. McClelland (Environmental Biology of Fishes, 2014)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Isolation and characterization of eight polymorphic microsatellite loci for Natterer’s bat, Myotis nattereri (Vespertilionidae, Chiroptera) - David D. Scott; Seán Fitzpatrick; Deborah A. Bailie; Emma S. M. Boston; Mathieu G. Lundy; Daniel J. Buckley; Emma C. Teeling; W. Ian Montgomery; Paulo A. Prodöhl (Conservation Genetics Resources, 2013)

Clinical and mutation data in 12 patients with the clinical diagnosis of Nager syndrome - J. C. Czeschik; C. Voigt; Y. Alanay; B. Albrecht; S. Avci; D. FitzPatrick; D. R. Goudie; U. Hehr; A. J. Hoogeboom; H. Kayserili; P. O. Simsek-Kiper; L. Klein-Hitpass; et al. (Human Genetics, 2013)

Doomed before they are described? The need for conservation assessments of cryptic species complexes using an amblyopsid cavefish (Amblyopsidae: Typhlichthys) as a case study - Matthew L. Niemiller; Gary O. Graening; Dante B. Fenolio; James C. Godwin; James R. Cooley; William D. Pearson; Benjamin M. Fitzpatrick; Thomas J. Near (Biodiversity and Conservation, 2013)

Low temperature constrains growth rates but not short-term ingestion rates of Antarctic ciliates - Julie M. Rose; Elizabeth Fitzpatrick; Annie Wang; Rebecca J. Gast; David A. Caron (Polar Biology, 2013)

Lethal Effects of Water Quality on Threatened California Salamanders but Not on Co‐Occurring Hybrid Salamanders - MAUREEN E. RYAN; JARRETT R. JOHNSON; BENJAMIN M. FITZPATRICK; LINDA J. LOWENSTINE; ANGELA M. PICCO; H. BRADLEY SHAFFER (Conservation Biology, 2013)
Biological invasions and habitat alteration are often detrimental to native species, but their interactions are difficult to predict. Interbreeding between native and introduced species generates novel genotypes and phenotypes, and human land use alters habitat structure and chemistry. Both invasions and habitat alteration create new biological challenges and opportunities. In the intensively farmed Salinas Valley, California (U.S.A.), threatened California tiger salamanders ( Ambystoma californiense ) have been replaced by hybrids between California tiger salamander and introduced barred tiger salamanders ( Ambystoma tigrinum mavortium ). We conducted an enclosure experiment to examine the effects habitat modification and relative frequency of hybrid and native California tiger salamanders have on recruitment of salamanders and their prey, Pacific chorus frogs ( Pseudacris regilla ). We tested whether recruitment differed among genetic classes of tiger salamanders (hybrid or native) and pond hydroperiod (seasonal or perennial). Roughly 6 weeks into the experiment, 70% (of 378 total) of salamander larvae died in 4 out of 6 ponds. Native salamanders survived ( n = 12) in these ponds only if they had metamorphosed prior to the die‐offs. During die‐offs, all larvae of native salamanders died, whereas 56% of hybrid larvae died. We necropsied native and hybrid salamanders, tested water quality, and queried the California Department of Pesticide Regulation database to investigate possible causes of the die‐offs. Salamander die‐offs, changes in the abundance of other community members (invertebrates, algae, and cyanobacteria), shifts in salamander sex ratio, and patterns of pesticide application in adjacent fields suggest that pesticide use may have contributed to die‐offs. That all survivors were hybrids suggests that environmental stress may promote rapid displacement of native genotypes . Efectos Letales de la Calidad del Agua sobre Salamandras de California Amenazadas pero no sobre Salamandras Híbridas Concurrentes

Hybridization between two gartersnake species (Thamnophis) of conservation concern: a threat or an important natural interaction? - John S. Placyk; Benjamin M. Fitzpatrick; Gary S. Casper; Randall L. Small; R. Graham Reynolds; Daniel W. A. Noble; Ronald J. Brooks; Gordon M. Burghardt (Conservation Genetics, 2012)

Does proximity to aquatic pollution affect reproductive traits in a wild‐caught intertidal fish? - N. M. Sopinka; J. L. Fitzpatrick; J. E. Taves; M. G. Ikonomou; S. E. Marsh‐Rollo; S. Balshine (Journal of Fish Biology, 2012)
How chronic exposure to aquatic pollution affects reproductive traits was assessed in nesting wild‐caught plainfin midshipman Porichthys notatus in areas with low and high contaminant exposure on Vancouver Island, British Columbia. Males in high‐exposure areas had a greater degree of testicular asymmetry, sperm with shorter heads and fewer live eggs in their nests. The results of this study provide important insights into the potential consequences of contaminant exposure on the reproductive physiology of wild‐caught fishes.

Assessing the potential for post‐copulatory sexual selection in elasmobranchs - J. L. Fitzpatrick; R. M. Kempster; T. S. Daly‐Engel; S. P. Collin; J. P. Evans (Journal of Fish Biology, 2012)
This review highlights the potential role that post‐copulatory sexual selection plays in elasmobranch reproductive systems and the utility of this group to further understanding of evolutionary responses to the post‐copulatory processes of sperm competition and cryptic female choice. The growing genetic evidence for female multiple mating (polyandry) in elasmobranchs is summarized. While polyandry appears to be common in this group, rates of multiple paternity are highly variable between species suggesting that there is large variance in the strength of post‐copulatory sexual selection among elasmobranchs. Possible adaptations of traits important for post‐copulatory sexual selection are then considered. Particular emphasis is devoted to explore the potential for sperm competition and cryptic female choice to influence the evolution of testes size, sperm morphology, genital morphology and sperm storage organs. Finally, it is argued that future work should take advantage of the wealth of information on these reproductive traits already available in elasmobranchs to gain a better understanding of how post‐copulatory sexual selection operates in this group.

New records for prehistoric introduction of Neotropical mammals to the West Indies: evidence from Carriacou, Lesser Antilles - Christina M. Giovas; Michelle J. LeFebvre; Scott M. Fitzpatrick (Journal of Biogeography, 2012)
Aim This paper investigates the prehistoric introduction of five mammalian taxa to Carriacou (Lesser Antilles) and refines the known anthropogenic ranges for these fauna in the pre‐Columbian West Indies. The importance of such records for understanding the region’s historical biogeography and ecology is considered. Location Carriacou Island, Grenada (12°28′ N, 61°26′ W). Methods Zooarchaeological assemblages from Carriacou’s earliest documented prehistoric sites, Grand Bay and Sabazan, were analysed, and exotic taxa were identified and quantified. The timing of introductions was established based on multiple radiocarbon assays, including three new accelerator mass spectrometry (AMS) direct dates obtained on the bone of exotic taxa. Source species and location(s) are considered and compared with known prehistoric records for the Caribbean to synthesize anthropogenic distributions for the pre‐Columbian period. The contexts of the zooarchaeological remains are evaluated to better understand the nature and purpose of introductions. Results Zooarchaeological investigation on Carriacou reveals the occurrence of multiple mammal introductions from South American between c . ad 700 and ad 1400. This paper presents the first records for guinea pig ( Cavia sp.), armadillo ( Dasypus sp.), peccary ( Tayassu/Pecari sp.), opossum ( Didelphis sp.) and agouti ( Dasyprocta sp.) from the island. Human‐mediated transport of these taxa is indicated by their absence from the record prior to human settlement of Carriacou. Several translocated species are either rare or entirely unknown for the region, and overall West Indian distributions are temporally and spatially discontinuous. Archaeological contexts indicate that mammalian introductions arose from human subsistence needs, but other social factors may have shaped the dispersal of these fauna. Main conclusions The taxonomic combination and richness of Carriacou’s introduced fauna are unusual within the region. Importantly, the new records significantly improve the known pre‐Columbian geographic range for peccary, guinea pig and armadillo. Integrated with regional records, these data augment our understanding of the Caribbean’s historical biogeography, and have the potential to improve our understanding of human mobility and anthropogenic environmental impacts in the West Indies prior to the arrival of Europeans.

Assimilation of water and dietary ions by the gastrointestinal tract during digestion in seawater-acclimated rainbow trout - Carol Bucking; John L. Fitzpatrick; Sunita R. Nadella; Iain J. McGaw; Chris M. Wood (Journal of Comparative Physiology B, 2011)

Assessing reef fish assemblage structure: how do different stereo-video techniques compare? - Dianne L. Watson; Euan S. Harvey; Ben M. Fitzpatrick; Timothy J. Langlois; George Shedrawi (Marine Biology, 2010)

Geography disentangles introgression from ancestral polymorphism in Lake Malawi cichlids - MERYL C. MIMS; C. DARRIN HULSEY; BENJAMIN M. FITZPATRICK; J. TODD STREELMAN (Molecular Ecology, 2010)
Phenotypically diverse Lake Malawi cichlids exhibit similar genomes. The extensive sharing of genetic polymorphism among forms has both intrigued and frustrated biologists trying to understand the nature of diversity in this and other rapidly evolving systems. Shared polymorphism might result from hybridization and/or the retention of ancestrally polymorphic alleles. To examine these alternatives, we used new genomic tools to characterize genetic differentiation in widespread, geographically structured populations of Labeotropheus fuelleborni and Metriaclima zebra . These phenotypically distinct species share mitochondrial DNA (mtDNA) haplotypes and show greater mtDNA differentiation among localities than between species. However, Bayesian analysis of nuclear single nucleotide polymorphism (SNP) data revealed two distinct genetic clusters corresponding perfectly to morphologically diagnosed L. fuelleborni and M. zebra . This result is a function of the resolving power of the multi‐locus dataset, not a conflict between nuclear and mitochondrial partitions. Locus‐by‐locus analysis showed that mtDNA differentiation between species ( F CT ) was nearly identical to the median single‐locus SNP F CT . Finally, we asked whether there is evidence for gene flow at sites of co‐occurrence. We used simulations to generate a null distribution for the level of differentiation between co‐occurring populations of L. fuelleborni and M. zebra expected if there was no hybridization. The null hypothesis was rejected for the SNP data; populations that co‐occur at rock reef sites were slightly more similar than expected by chance, suggesting recent gene flow. The coupling of numerous independent markers with extensive geographic sampling and simulations utilized here provides a framework for assessing the prevalence of gene flow in recently diverged species.

Gene flow between an endangered endemic iguana, and its wide spread relative, on the island of Utila, Honduras: when is hybridization a threat? - Stesha A. Pasachnik; Benjamin M. Fitzpatrick; Thomas J. Near; Arthur C. Echternacht (Conservation Genetics, 2009)

The effect of elbow joint centre displacement on force generation and neural excitation - Emer P. Doheny; Madeleine M. Lowery; Mark J. O’Malley; David P. FitzPatrick (Medical & Biological Engineering & Computing, 2009)

Climatic drivers of hemispheric asymmetry in global patterns of ant species richness - Robert R. Dunn; Donat Agosti; Alan N. Andersen; Xavier Arnan; Carsten A. Bruhl; Xim Cerdá; Aaron M. Ellison; Brian L. Fisher; Matthew C. Fitzpatrick; Heloise Gibb; Nicholas J. Gotelli; Aaron D. Gove; et al. (Ecology Letters, 2009)
Although many taxa show a latitudinal gradient in richness, the relationship between latitude and species richness is often asymmetrical between the northern and southern hemispheres. Here we examine the latitudinal pattern of species richness across 1003 local ant assemblages. We find latitudinal asymmetry, with southern hemisphere sites being more diverse than northern hemisphere sites. Most of this asymmetry could be explained statistically by differences in contemporary climate. Local ant species richness was positively associated with temperature, but negatively (although weakly) associated with temperature range and precipitation. After contemporary climate was accounted for, a modest difference in diversity between hemispheres persisted, suggesting that factors other than contemporary climate contributed to the hemispherical asymmetry. The most parsimonious explanation for this remaining asymmetry is that greater climate change since the Eocene in the northern than in the southern hemisphere has led to more extinctions in the northern hemisphere with consequent effects on local ant species richness.

The strontium content of roe collected from spawning brown trout Salmo trutta L. reflects recent otolith microchemistry - E. M. Waite; G. P. Closs; J. Kim; B. Barry; A. Markwitz; R. Fitzpatrick (Journal of Fish Biology, 2008)
The relationship between the strontium content of the outer layers of otoliths (an indication of recent marine, estuarine or riverine habitat use) and the strontium content of roe in ripe female brown trout Salmo trutta was examined in fish collected from the Pomahaka River and the lower reaches of the Clutha River, South Island, New Zealand. A close relationship was found between the strontium content of roe and the outer layers of otoliths. This finding suggests that spawned eggs collected from redds could potentially be used to track the extent of upstream spawning migrations by anadromous brown trout.

Congruent population structure inferred from dispersal behaviour and intensive genetic surveys of the threatened Florida scrub‐jay ( Aphelocoma cœrulescens ) - A. COULON; J. W. FITZPATRICK; R. BOWMAN; B. M. STITH; C. A. MAKAREWICH; L. M. STENZLER; I. J. LOVETTE (Molecular Ecology, 2008)
The delimitation of populations, defined as groups of individuals linked by gene flow, is possible by the analysis of genetic markers and also by spatial models based on dispersal probabilities across a landscape. We combined these two complimentary methods to define the spatial pattern of genetic structure among remaining populations of the threatened Florida scrub‐jay, a species for which dispersal ability is unusually well‐characterized. The range‐wide population was intensively censused in the 1990s, and a metapopulation model defined population boundaries based on predicted dispersal‐mediated demographic connectivity. We subjected genotypes from more than 1000 individual jays screened at 20 microsatellite loci to two Bayesian clustering methods. We describe a consensus method for identifying common features across many replicated clustering runs. Ten genetically differentiated groups exist across the present‐day range of the Florida scrub‐jay. These groups are largely consistent with the dispersal‐defined metapopulations, which assume very limited dispersal ability. Some genetic groups comprise more than one metapopulation, likely because these genetically similar metapopulations were sundered only recently by habitat alteration. The combined reconstructions of population structure based on genetics and dispersal‐mediated demographic connectivity provide a robust depiction of the current genetic and demographic organization of this species, reflecting past and present levels of dispersal among occupied habitat patches. The differentiation of populations into 10 genetic groups adds urgency to management efforts aimed at preserving what remains of genetic variation in this dwindling species, by maintaining viable populations of all genetically differentiated and geographically isolated populations.

Anthropogenic impacts to coral reefs in Palau, western Micronesia during the Late Holocene - S. M. Fitzpatrick; T. J. Donaldson (Coral Reefs, 2007)

Novel titanocene anti-cancer drugs and their effect on apoptosis and the apoptotic pathway in prostate cancer cells - K. O'Connor; C. Gill; M. Tacke; F.-J. K. Rehmann; K. Strohfeldt; N. Sweeney; J. M. Fitzpatrick; R. W. G. Watson (Apoptosis, 2006)

Seroprevalence Estimation and Risk Factors for A. marginale on Smallholder Dairy Farms in Tanzania - E. S. Swai; E. D. Karimuribo; N. H. Ogden; N. P. French; J. L. Fitzpatrick; M. J. Bryant; D. M. Kambarage (Tropical Animal Health and Production, 2005)

A Cross-sectional Study of Reproductive Performance of Smallholder Dairy Cows in Coastal Tanzania - E. S. Swai; M. J. Bryant; E. D. Karimuribo; N. P. French; N. H. Ogden; J. L. Fitzpatrick; D. M. Kambarage (Tropical Animal Health and Production, 2005)

Chemical reduction causing land degradation. II Detailed observations at a discharge site in the Eastern Dundas Tablelands, Victoria, Australia - W. K. Gardner; J. D. Fawcett; R. W. Fitzpatrick; R. M. Norton; M. Trethowan (Plant and Soil, 2004)

Chemical reduction causing land degradation. I Overview - W. K. Gardner; J. D. Fawcett; R. W. Fitzpatrick; R. M. Norton (Plant and Soil, 2004)

Differentiation-induced HL-60 cell apoptosis: A mechanism independent of mitochondrial disruption? - B. T. Doyle; A. J. O’Neill; J. M. Fitzpatrick; R. W. G. Watson (Apoptosis, 2004)

Gonad Organochlorine Concentrations and Plasma Steroid Levels in White Sturgeon ( Acipenser transmontanus ) from the Columbia River, USA - E. P. Foster; M. S. Fitzpatrick; G. W. Feist; C. B. Schreck; J. Yates (Bulletin of Environmental Contamination and Toxicology, 2001)

Essential genes in proximal 3L heterochromatin of Drosophila melanogaster - S. Schulze; D. A. R. Sinclair; E. Silva; K. A. Fitzpatrick; M. Singh; V. K. Lloyd; K. A. Morin; J. Kim; D. G. Holm; J. A. Kennison; B. M. Honda (Molecular Genetics and Genomics, 2001)

In Vitro Earthworm Lumbricus terrestris Coelomocyte Assay for Use in Terrestrial Toxicity Identification Evaluation - S. W. Burch; L. C. Fitzpatrick; A. J. Goven; B. J. Venables; M. A. Giggleman (Bulletin of Environmental Contamination and Toxicology, 1999)

Wound Healing in Earthworms Lumbricus terrestris: A Cellular-Based Biomarker for Assessing Sublethal Chemical Toxicity - M. A. Cikutovic; L. C. Fitzpatrick; A. J. Goven; B. J. Venables; M. A. Giggleman; E. L. Cooper (Bulletin of Environmental Contamination and Toxicology, 1999)

Equine herpesvirus genomes: Heterogeneity of naturally occurring type 4 isolates and of a type 1 isolate after heterologous cell passage - M. J. Studdert; D. R. Fitzpatrick; G. F. Browning; A. A. Cullinane; J. M. Whalley (Archives of Virology, 1986)